PERLINDUNGAN HUKUM KREDITUR TERHADAP DEBITUR YANG PAILIT KARENA FORCE MAJEURE - Afad Pratama Usasra; Nur Hakim; Roni Pandiangan (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Bankruptcy is a legal mechanism intended to provide legal certainty and fairness for the parties involved, particularly creditors and debtors, in situations where the debtor is unable to fulfill debt obligations. However, in practice, bankruptcy caused by force majeure raises specific legal issues, especially regarding the form and scope of legal protection for creditors. Conditions of force majeure may place the debtor in a position of non-performance without fault, which potentially creates an imbalance of interests between creditors and debtors. The method used in this research is normative legal research, conducted as an effort to obtain the necessary data related to the problem. The data used are secondary data and tertiary legal materials. In addition, primary data is also used to support the secondary legal materials. Data analysis is conducted using qualitative legal analysis methods. The theories used in this research are the Legal Protection Theory and the Risk Theory. The results of the study indicate that legal protection for creditors in bankruptcy caused by force majeure is still provided through the principle of paritas creditorum and the mechanism of bankruptcy estate settlement conducted by the curator. However, the Bankruptcy Law has not explicitly regulated differentiated treatment for debtors who become bankrupt without fault. Therefore, equitable legal interpretation and more comprehensive legal policies are required to ensure a balance of rights and obligations between creditors and debtors in bankruptcy situations caused by force majeure.